2015
DOI: 10.5888/pcd12.140133
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Tobacco Advertisements at SNAP and WIC Stores, Philadelphia, Pennsylvania, 2012

Abstract: IntroductionTobacco advertising is widespread in urban areas with racial/ethnic minority and low-income households that participate in nutrition assistance programs. Tobacco sales and advertising are linked to smoking behavior, which may complicate matters for low-income families struggling with disparate health risks relating to nutrition and chronic disease. We investigated the relationship between the amount and type of tobacco advertisements on tobacco outlets and the outlet type and location.MethodsBy usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Research suggests that racial and socioeconomic inequities persist in the residential proximity to, and density of, stores selling tobacco and alcohol. Many U.S.-based studies at the state, metropolitan area, and county levels have found that stores selling tobacco are disproportionately located in neighborhoods with higher percentages of minorities, particularly African Americans and Hispanics [ 52 , 53 , 54 ], and lower income [ 55 , 56 , 57 ]. Similar patterns of racial and economic inequity have been found for alcohol outlets [ 58 , 59 , 60 ].…”
Section: Characteristics Of Risky Substance Use Environmentsmentioning
confidence: 99%
“…Research suggests that racial and socioeconomic inequities persist in the residential proximity to, and density of, stores selling tobacco and alcohol. Many U.S.-based studies at the state, metropolitan area, and county levels have found that stores selling tobacco are disproportionately located in neighborhoods with higher percentages of minorities, particularly African Americans and Hispanics [ 52 , 53 , 54 ], and lower income [ 55 , 56 , 57 ]. Similar patterns of racial and economic inequity have been found for alcohol outlets [ 58 , 59 , 60 ].…”
Section: Characteristics Of Risky Substance Use Environmentsmentioning
confidence: 99%
“…Among SNAP recipients, agency-influencing contexts may include living with unemployment or poverty wages, amenity-poor neighborhoods, low mobility, and high exposure to unhealthy food and beverage advertising (Gray et al, 2016; Hillier, 2012). Indeed, some researchers suggest that poverty is the most influential contextual factor on food choices, and that healthy food affordability poses a significant and critical barrier (Drewnowski & Eichelsdoerfer, 2010).…”
Section: Reduced Agency: An Ethical Risk Of Item Restrictionmentioning
confidence: 99%
“…Moreover, tobacco companies have specifically marketed to marginalized groups with higher smoking rates (7, 8). Currently, most tobacco advertising occurs at point-of-sale locations such as convenience stores (8), and is concentrated in poor neighborhoods (13, 16). It is likely that individuals with SUDs are among those who frequent locations with a high concentration of tobacco ads and promotional item marketing.…”
Section: Introductionmentioning
confidence: 99%